Thermal and Morphological Assessment of the Penta-Layered, Hybrid U-Polyester Composite Reinforced with Glass Fibers and Polypropylene - Md. Shahin Akanda; Md. Shariful Islam; Md. Ali Akbar; A. M. Sarwaruddin Chowdhury; M. A. Gafur; Md. Sahab Uddin (Advances in Materials Science and Engineering)
The interaction between the fibers and matrix in a fiber-reinforced polymer composite material is important in figuring out its properties. The incorporation of fibers with polymers can result in composites with enhanced strength and stiffness. This study aims to investigate the thermal and morphological characteristics of hybrid u-polyester composites reinforced with glass fibers and polypropylene. The fabrication of composite specimens was conducted through a straightforward cold press method. The compositions of the composites were held constant, except for the orientation of the glass fibers and polypropylene. In this study, the TG/DTG technique was used to analyze the thermal characteristics of the composites. In addition, transverse thermal conductivity was measured using the ASTM E1530 method. The test results showed that the composite reinforced with glass fibers exhibited the lowest weight loss and minimal thermal conductivity among all the samples, followed by the hybrid composite. Based on the TGA curves of the samples, the matrix experienced a weight loss of 9.7% at a temperature of 300°C, which reduced to 2.6% and 2.1% for hybrid composites and glass fiber-reinforced composites, respectively. DTG curves for composites demonstrate that the hybrid and fiber-reinforced composites degraded at rates of 0.64 mg/min and 0.36 mg/min, respectively, at 392.3°C and 395.7°C. Moreover, transverse thermal conductivity of the composite which consists of five-glass-fibered layers shows a minimal thermal conductivity of 0.05 W/m·K. The morphological properties were also investigated using scanning electron microscopy (SEM) and Fourier-transform infrared spectroscopy (FTIR). The findings from SEM and FTIR showed that a higher proportion of glass fibers led to a more oriented composite structure, demonstrating enhanced crosslinking between fibers and polyester. Therefore, the insights of this study can be used to improve the performance of glass fibers and polypropylene hybrid-laminated composites intended for high-temperature applications.